Locating Indigenous Knowledge Systems: Discourse on Corruption in Zimbabwe - Jenjekwa, Vincent (Fresno Calif.]: California Institute of Pan African Studies, 2022)
In the interest of Zimbabwe’s socio-economic transformation agenda, the scourge of corruption has to be stopped. This paper sought to accurately locate African indigenous knowledge systems focused specifically on Shona proverbs in the ongoing discourse on corruption. It is observed that indigenous knowledge systems do not condone corruption. The research established here is that any reference to African indigenous knowledge systems to justify corruption is a blatant misreading and abuse of African (Shona) indigenous knowledge. Thus, it is recommended that all citizens embrace the values of hunhuism (an African philosophy) in word and in deed for an sustainable socio-economic transformation. The paper is inspired by Afrocentric reasoning and therefore, made use of in-depth interview and critical text analysis in its methodology.